Transfer of the EFE-5 Executive Function Intervention Program to the Reduction of Behavioral Problems. - Romero-López, Miriam; Pichardo, Carmen; Sastre-Riba, Sylvia; Cano-García, Francisco (Children, 2025)
Background/Objectives: Numerous research studies link the improvement in executive functions and school success. However, there is hardly any research analyzing the transfer of this improvement to behavioral problems. This study analyzed whether improving executive functions, through contextualized daily activities, decreases these behaviors. Methods: Fifty third-year kindergarten students participated, divided into experimental and active control groups, with pre- and post-intervention measurements. The students in the experimental group were trained with the EFE-P program and the students in the control group received regular curriculum activities. The EFE-P program (i) has been designed with the aim of improving their executive functions, using a game-based approach; (ii) not only involves cognitive activities, but also behavioral and emotional activities, related to the warm aspects of executive functions; and (iii) consists of three units (inhibitory control, working memory and cognitive flexibility), with each unit involving 7 sessions (21 sessions in total), with an approximate duration of 30 min each. Results: Analysis of the data using a generalized linear mixed effects model revealed that students in the experimental group scored lower for behavioral problems than those in the active control group and the effect sizes were large for all of them: aggressiveness (d = 1.25); hyperactivity (d = 0.77); attention deficit (d = 1.12); anxiety (d = 0.82); and depression (d = 1.51). Conclusions: After discussing the results, it is concluded that intervention in executive functions induces, by way of distant transfer, a decrease in behavioral problems in preschool; the role of contextualized activities in real situations is emphasized; and several implications for practice and research are discussed.